Phytochemicals as Treatment for Allergic Asthma: Therapeutic Effects and Mechanisms of Action - Echeverria-Morgado, J (Elsevier GmbH, 2024)
Background: Allergic asthma is an inflammatory disease caused by the immune system s reaction to allergens, inflammation and narrowing of the airways, and the production of more than normal mucus. One of the main reasons is an increased production of inflammatory cytokines in the lungs that leads to the appearance of symptoms of asthma, including inflammation and shortness of breath. On the other hand, it has been proven that phytochemicals with their antioxidant and anti-inflammatory properties can be useful in improving allergic asthma. Purpose: Common chemical treatments for allergic asthma include corticosteroids, which have many side effects and temporarily relieve symptoms but are not a cure. Therefore, taking the help of natural compounds to improve the quality of life of asthmatic patients can be a valuable issue that has been evaluated in the present review. Study design and Methods: In this study, three databases (Scopus, PubMed, and Cochrane) with the keywords: allergic asthma, phytochemical, plant, and herb were evaluated. The primary result was 5307 articles. Non-English, repetitive, and review articles were deleted from the study. Results and discussion: Finally, after carefully reading the articles, 102 were included in the study (2006–2022). The results of this review state that phytochemicals suppress the inflammatory pathways via inhibition of inflammatory cytokines production/secretion, genes, and proteins involved in the inflammation process, reducing oxidative stress indicators and symptoms of allergic asthma, such as cough and mucus production in the lungs. Conclusion: With their antioxidant effects, this study concluded that phytochemicals suppress cytokines and other inflammatory indicators and thus can be considered an adjunctive treatment for improving allergic asthma. © 2023